Assessment of Heavy Metals in Water, Fish and Sediments of the Baleh River, Sarawak, Malaysia - Hui, Ping Chai; Lee, Nyanti; Jongkar, Grinang; Teck-Yee, Ling; Siong-Fong, Sim (Universiti Malaysia Sarawak (UNIMAS), 2018)
This paper reports the heavy metals content in water, sediments and in fish of the Baleh River, in order to evaluate the contamination status of metals. Water and sediment samples were obtained from seven stations located upstream of the Baleh River. Fish species were collected using netting and three species were recorded. Samples were digested and subjected to metal analysis. The findings indicate that there is low risk of metal contamination in water and sediments. Nonetheless some stations were characterized by higher levels of Fe, Al and Mn in water, likely due to accelerated sediment runoff. The acid extractable metal content reported in this study represents the dissolved and weakly-sorbed metals on particulates. For fish, accumulation of heavy metals was found to be more pronounced in the gills, compared to dorsal and ventral muscles. The concentration of Fe, Mn and Al were particularly high in the gills, as these elements were abundant in water. Hg on the other hand was consistently higher in dorsal and ventral muscles. Generally, concentrations of heavy metals in fishes of the Baleh were well within the permissible limit of Food and Agriculture Organization